2019
DOI: 10.5194/hess-2018-585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection of multi-model ensemble of GCMs for the simulation of precipitation based on spatial assessment metrics

Abstract: Abstract. The climate modelling community has trialled a large number metrics to evaluate the temporal performance of the Global Circulation Models (GCMs) for the selection of GCMs, while very little attention has been given to spatial performance of GCMs which is equally important. This study evaluated the performance of 20 Coupled Model Intercomparison Project 5 (CMIP5) GCMs pertaining to their skills in simulating mean annual, monsoon and winter precipitation over Pakistan using state-of-the-art spatial met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Future temperature data (years 2050 and 2070) in the present study were used from the ensemble of eight general circulation models (GCMs) (BCC-CSM1-1; GISS-ER-R; HADGEM2-AO; HadGEM2-ES; IPSL-CM5A-MR; MIROC-ESM-CHEM; MRI-CGCM3; Nor-ESM1-M) and four greenhouse gas concentration trajectories scenarios (RCP 2.6, RCP 4.5, RCP 6.0, RCP 8.5) as proposed in the Fifth Assessment of the Intergovernmental Panel for Climate Change to reduce GCM and scenario-based uncertainties (CMIP5) (Moss et al, 2010). A simple arithmetic average of the ensemble members with equal weight is generally more reliable over a single model approach (Her et al, 2016;Kim et al, 2016;Ahmed et al, 2019). Therefore, in the present study, we used an arithmetic average ensemble of eight GCMs.…”
Section: Temperature Data For Calculation Of Risk Indicesmentioning
confidence: 99%
“…Future temperature data (years 2050 and 2070) in the present study were used from the ensemble of eight general circulation models (GCMs) (BCC-CSM1-1; GISS-ER-R; HADGEM2-AO; HadGEM2-ES; IPSL-CM5A-MR; MIROC-ESM-CHEM; MRI-CGCM3; Nor-ESM1-M) and four greenhouse gas concentration trajectories scenarios (RCP 2.6, RCP 4.5, RCP 6.0, RCP 8.5) as proposed in the Fifth Assessment of the Intergovernmental Panel for Climate Change to reduce GCM and scenario-based uncertainties (CMIP5) (Moss et al, 2010). A simple arithmetic average of the ensemble members with equal weight is generally more reliable over a single model approach (Her et al, 2016;Kim et al, 2016;Ahmed et al, 2019). Therefore, in the present study, we used an arithmetic average ensemble of eight GCMs.…”
Section: Temperature Data For Calculation Of Risk Indicesmentioning
confidence: 99%
“…Using this validation-based approach, we are assuming that a model's ability to simulate an observed baseline climate will be representative of the same model's ability to project future climate. The selection of GCMs has been analyzed in a number of studies (e.g., [41,53,54]). However, there is not yet sufficient scientific consensus with respect to both the identification of unsatisfactory models, and the relation between apparently poor performance to the plausibility of future projections [55].…”
Section: Selection Of Climate Change Modelsmentioning
confidence: 99%
“…The multi-model ensemble is a method created by multiple model simulations. Considering the summary by several previous studies, this method can reduce the biases and uncertainties of the simulations associated with GCMs ( Ahmed et al., 2018 ; He et al., 2019 ; Raju and Kumar, 2020 ; Yan et al., 2015 ). In addition, several researchers have demonstrated that the multi-model ensemble method can improve climate simulation performance compared to single models ( Chhin and Yoden, 2018 ; Hughes et al., 2014 ; Kamworapan and Surussavadee, 2019 ; Raju and Kumar, 2014 , 2015 ).…”
Section: Methodsmentioning
confidence: 99%